1988
DOI: 10.3147/jsfp.23.147
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of the virus isolated from the gill of clam, Meretrix lusoria.

Abstract: The electron microscopic examination of the abnormally dark regions of the gill from hard clam, Meretrix lusoria, revealed that there were virus-like particles present in the cytoplasm of necrotic cells. With TO-2 cell line, the virus was isolated. Electron microscopic examinations showed that there were no detactable differences in morphology and location of virions in the gill cells of clam and TO-2 cells except that virus crystals were infrequently observed in clam gills. The subsequent serological and bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 16 publications
0
35
0
Order By: Relevance
“…In spite of the wide spread monitoring for aquatic birnaviruses in the freshwater and marine environments, only recently the IPNV American serotype (WB) has been isolat ed from turbot in Europe (Novoa et al, 1993b). Furthermore birnaviruses have been isolated from marine bivalves (Underwood et al, 1977;Lo et al, 1988;Rivas et al, 1993) and even from several species used as food for cultured fish. This is the case of rotifer (Brachionus plicatilis), other cultured marine fish larvae, and the fish species used as fresh food for turbot such as raw sand-eel (Ammodytes sp) and blue whiting (Micromesistius potassou) (Rivas et al, 1993).…”
Section: Viral Rna Electrophoresismentioning
confidence: 99%
“…In spite of the wide spread monitoring for aquatic birnaviruses in the freshwater and marine environments, only recently the IPNV American serotype (WB) has been isolat ed from turbot in Europe (Novoa et al, 1993b). Furthermore birnaviruses have been isolated from marine bivalves (Underwood et al, 1977;Lo et al, 1988;Rivas et al, 1993) and even from several species used as food for cultured fish. This is the case of rotifer (Brachionus plicatilis), other cultured marine fish larvae, and the fish species used as fresh food for turbot such as raw sand-eel (Ammodytes sp) and blue whiting (Micromesistius potassou) (Rivas et al, 1993).…”
Section: Viral Rna Electrophoresismentioning
confidence: 99%
“…Subsequently, birnaviruses were found all over the world in other fishes such as eels, yellowtail, turbot, goby, and shellfishes (Sano 1976, Adair & Ferguson 1981, Hudson et al 1981, Sorimachi & Egusa 1982, Hedrick et al 1985, 1986, Sorimach & Hara 1985, Lo et al 1988, Wattanavijan et al 1988, Lipipun et al 1989, Nova et al 1993, Suzuki et al 1998a. The serological relationships between IPNV and other aquatic birnaviruses were studied using cross-neutralization tests with polyclonal and monoclonal antibodies, which resulted in the establishment of 2 or 3 serogroups (Hill & Way 1988, Wolf 1988, Caswell-Reno et al 1989, Kusuda et al 1993.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies indicated that marine bivalves are also common hosts of IPNV (Dobos et al, 1979;Lo et al, 1988 , 1978;Kennedy and MacDonald, 1982;Lo et al, 1990;MacDonald, 1978;MacDonald and Kennedy, 1979;MacDonald and Yamamoto, 1978;Malsberger and Cerini, 1963;Nicholson and Dunn, 1974). Most of the above studies indicated that defective interfering (DI) par ticles were involved in IPNV viral interference.…”
Section: Infectious Pancreatic Necrosis Virus (Ipnv) Ismentioning
confidence: 99%